Complete Home Smoking Bans and Antitobacco Contingencies: A Natural Experiment. Issue 2 (2nd September 2013) - Hovell, Melbourne F.; Adams, Marc A.; Hofstetter, C. Richard; Martínez-Donate, Ana P.; González-Pérez, Guillermo J.; Rovniak, Liza S.; Boman-Davis, Marie C.
Abstract: Introduction: The California antitobacco culture may have influenced home smoking bans in Mexico. Based on the Behavioral Ecological Model, exposure to socially reinforcing contingencies or criticism may explain adoption of home smoking bans in Tijuana, Mexico, approximating rates relative to San Diego, California, and higher than those in Guadalajara, Mexico. Methods: A representative cross-sectional population survey of Latinos ( N = 1, 901) was conducted in San Diego, Tijuana, and Guadalajara between June 2003 and September 2004. Cities were selected to represent high-, medium-, and low-level exposure to antitobacco social contingencies of reinforcement in a quasiexperimental analysis of possible cultural influences across borders. Results: Complete home smoking ban prevalence was 91% in San Diego, 66% in Tijuana, and 38% in Guadalajara ( p < .001). Sample cluster-adjusted logistic regression showed significantly lower odds of complete home smoking bans in Guadalajara (odds ratio [ OR ] = .048) and in Tijuana ( OR = .138) compared to San Diego after control for demographics. Odds of complete home smoking bans in both Guadalajara and Tijuana in comparison with San Diego were weakened when mediators for bans were controlled in predictive models. Direction of association was consistent with theory. When theoretical mediators were explored as possible moderators, weak and nonsignificant associations were obtained for all interaction terms. Bootstrap analyses demonstrated that our multivariable logistic regression results were reliable. Conclusions: Results suggest that California antismoking social contingencies mediate complete home smoking bans in all 3 cities and may account for the greater effects in Tijuana contrasted with Guadalajara.